Therapeutic Options in Idiopathic Burning Mouth Syndrome: Literature Review - Miziara,Ivan (2015)
Introduction Burning mouth syndrome (BMS) is characterized by a burning sensation in the tongue, palate, lips, or gums of no well-defined etiology. The diagnosis and treatment for primary BMS are controversial. No specific laboratory tests or diagnostic criteria are well established, and the diagnosis is made by excluding all other possible disorders. Objective To review the literature on the main treatment options in idiopathic BMS and compare the best results of the main studies in 15 years. Data Synthesis We conducted a literature review on PubMed/MEDLINE, SciELO, and Cochrane-BIREME of work in the past 15 years, and only selected studies comparing different therapeutic options in idiopathic BMS, with preference for randomized and double-blind controlled studies. Final Comments Topical clonazepam showed good short-term results for the relief of pain, although this was not presented as a definitive cure. Similarly, α-lipoic acid showed good results, but there are few randomized controlled studies that showed the longterm results and complete remission of symptoms. On the other hand, cognitive therapy is reported as a good and lasting therapeutic option with the advantage of not having side effects, and it can be combined with pharmacologic therapy.